PENGARUH KECERDASAN EMOSIONAL TERHADAP ETHICAL BEHAVIOR - Christien A. Karambut; Daisy I. Erny Sundah; Jacob T. S. Makapedua; Grace J. S. N. Rumimper (Manis: Jurnal Manajemen dan Bisnis, 2020)
The world of education cannot be separated from an ethic that regulates the situation and conditions of education actors. One of the factors that influence ethical behavior is emotional intelligence. Emotional intelligence is a person's basic intelligence in thought and behavior. The purpose of this study was to examine the effect of emotional intelligence on ethical behavior and to determine the level of emotional intelligence and ethical behavior of lecturers at the Manado State Polytechnic Department of Business Administration. This type of research is quantitative with survey methods and sampling techniques using saturated samples or census. The population is 54 lecturers spread across the Business Management, Business Administration and Marketing Management study programs. Dissemination of the questionnaire using google form. The response rate of this study was 81.5%. Data analysis technique using regression. The results of this study stated that the level of emotional intelligence and ethical behavior of the lecturers of the Department of Business Administration was categorized as high or good. In addition, the results of this study also explain that emotional intelligence has a significant effect on ethical behavior.